A Tale of Two Tariff Commissions and One Dubious 'Globalization Backlash' - Stephen Meardon (Inter-American Development Bank, Research Department, 2006)
During much of the previous era of globalization, from the 1860s until the First World War, U. S. tariffs were surprisingly high. Present-day economic historians have suggested that U. S. protection as the result of a backlash against globalization that was the beginning of its decline. They have also argued that the backlash holds a lesson for the present: specifically, that we must attend to the distributive inequities that globalization engenders, or else globalization will again plant the seeds of its own destruction. I show that U. S. tariffs were not the product of backlash. A history of economic ideas in the nineteenth century United States, centered on two tariff commissions in 1866-1870 and 1882, reveals that the ideas debated in intellectual and policy circles alike bore no trace of globalization backlash. The important feature of U. S. intellectual and tariff policy history is not globalization backlash, but rather the absence from most historical accounts of certain thinkers and ideas that were crucial to the debate. Accordingly, the lesson that history holds for the present is not that we must attend to globalization`s inequities. (That lesson is likely to stand or fall apart from history. ) Instead it is that we need to attend to the /idea/ of backlash, which has a foothold in history that is deeper than the evidence. The lesson implies that to understand the present and future of globalization, what are required are histories of ideas.
Keywords: 330; Zollpolitik; Handelsgeschichte; Globalisierung; Protektionismus; USA